1996
DOI: 10.1155/1997/270179
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnosis for Giardia Lamblia Infection: A Comparison of Microscopy, Coprodiagnosis and Serology

Abstract: MA BEHR, E KOKOSKIN, TW GYORKOS, L CÉDILOTTE, GM FAUBERT, JD MACLEAN. Laboratory diagnosis for MAIN RESULTS:For 152 previously collected stools, copro-antigen detection had a sensitivity of 73 of 74 (98.6%) and a specificity of 78 of 78 (100%). In clinical samples of 62 patients, eight of the 62 patients (13%) were diagnosed with G lamblia infection on microscopy. Copro-antigen diagnosis was accurate in symptomatic patients, with sensitivity of seven of eight (87.5%) and specificity of 52 of 54 (96.8%). Serolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…Faubert, 2000). According to Faubert (2000), all studies using the ELISA-GSA 65 antigen report greater sensitivity with ELISA than microscopy on a single specimen, and the sensitivity varies between 95 and 100%, with 100% specifi city reported when used with stools from patients infected with various intestinal parasites (Behr et al, 1997;Rosoff and Stibbs, 1986). According to Faubert (2000), all studies using the ELISA-GSA 65 antigen report greater sensitivity with ELISA than microscopy on a single specimen, and the sensitivity varies between 95 and 100%, with 100% specifi city reported when used with stools from patients infected with various intestinal parasites (Behr et al, 1997;Rosoff and Stibbs, 1986).…”
Section: Antigen Detection Using Antibodies Labelled With Fluorescentmentioning
confidence: 99%
“…Faubert, 2000). According to Faubert (2000), all studies using the ELISA-GSA 65 antigen report greater sensitivity with ELISA than microscopy on a single specimen, and the sensitivity varies between 95 and 100%, with 100% specifi city reported when used with stools from patients infected with various intestinal parasites (Behr et al, 1997;Rosoff and Stibbs, 1986). According to Faubert (2000), all studies using the ELISA-GSA 65 antigen report greater sensitivity with ELISA than microscopy on a single specimen, and the sensitivity varies between 95 and 100%, with 100% specifi city reported when used with stools from patients infected with various intestinal parasites (Behr et al, 1997;Rosoff and Stibbs, 1986).…”
Section: Antigen Detection Using Antibodies Labelled With Fluorescentmentioning
confidence: 99%
“…In Table 1, the results obtained by different laboratories with a variety of serological assays for the detection of Giardia antibodies in serum of proven cases are summarized. Proven cases of giardiasis were defined as follows: "patients passing cysts in their feces and/or presenting with one or more of the clinical symptoms of giardiasis" (15).…”
Section: Immunodiagnosismentioning
confidence: 99%
“…In fact, all studies with the ELISA-GSA 65 have reported a greater sensitivity of the immunodiagnosis assay over the microscopic examination of a single specimen ( Table 1). The sensitivity of the assay varies between 95 and 100%, and 100% specificity has been reported when it was used with stools from patients infected with other intestinal parasites (15,162). It has been reported that the ELISA-GSA 65 can detect Giardia infection in at least 30% more cases than the microscopic examination (163).…”
Section: Detection Of Antigens In Fecesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is distributed worldwide with an estimated global prevalence of 280 million cases per annum [2]. Its mode of transmission is faeco-oral due to consumption of contaminated food or water or by person to person contact in homosexuals [3]. G. lamblia infection generally causes a varied spectrum of disease ranging from the asymptomatic carrier state to acute fulminating diarrhoea or persistent diarrhoea with malabsorption in children and adults [4].…”
Section: Introductionmentioning
confidence: 99%